Single Domain Antibody application in bacterial infection diagnosis and neutralization - Qin, Qian; Liu, Hao; He, Wenbo; Guo, Yucheng; Zhang, Jiaxin; She, Junjun; Zheng, Fang; Zhang, Sicai; Muyldermans, Serge; Wen, Yurong (Frontiers in Immunology, 2022)
The increasing antibiotic resistance makes that bacterial infections cause a serious threat to human health. Efficient detection and treatment strategies are the keys to preventing and reducing bacterial infections. Due to the high affinity and antigen specificity, antibodies have become an important tool for diagnosis and treatment of various human diseases. In addition to conventional antibodies, a unique class of “heavy-chain-only” antibodies (HCAbs) were found in the serum of camelids and sharks. HCAbs binds to the antigen through only one variable domain referred to VHH (variable domain of the heavy chain of HCAbs). The recombinant format of the VHH is also called single domain antibody (sdAb) or nanobody (Nb). Sharks might also have an ancestor HCAb from where SdAbs or V-NAR might be engineered. Compared with traditional Abs, Nbs have several outstanding properties such as small size, high stability, strong antigen-binding affinity, high solubility and low immunogenicity. Furthermore, they are expressed at low cost in microorganisms and amenable to engineering. These superior properties make Nbs a highly desired alternative to con 0ventional antibodies, which are extensively employed in structural biology, unravelling biochemical mechanisms, molecular imaging, diagnosis and treatment of diseases. In this review, we summarized recent progress of nanobody-based approaches in diagnosis and neutralization of bacterial infection and further discussed the challenges of Nbs in these fields.